1996
DOI: 10.1002/pro.5560050415
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase homology modeling using the inverse protein folding approach

Abstract: Xylanase has been used in wood pulp bleaching in an effort to reduce chlorine release into the environment and pollution associated with paper production. The three-dimensional structure of xylanase is important to enable better understanding of the enzyme mechanism and to help design a more thermostable xylanase mutant. At the time this work was begun, there was no sequence homologous protein available for traditional sequence-based homology modeling. In order to circumvent this problem, the inverse protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In comparative modeling, manual adjustments of sequence alignments are used in model building 71. When sequence‐structure alignments generated from fold recognition methods are not suitable for modeling, alignments are made by visual examination of the secondary structural patterns of the target sequence and the template structure 72. To be consistent with most of the threading results of other B30.2‐like domains, we built a model of pyrin based on two Ig‐like folds to infer potential functional sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In comparative modeling, manual adjustments of sequence alignments are used in model building 71. When sequence‐structure alignments generated from fold recognition methods are not suitable for modeling, alignments are made by visual examination of the secondary structural patterns of the target sequence and the template structure 72. To be consistent with most of the threading results of other B30.2‐like domains, we built a model of pyrin based on two Ig‐like folds to infer potential functional sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It showed that structurally conserved regions were reasonably well modeled while non-homologous regions were not. Conformational analysis on numerous modeled structures and their subsequently X-ray determined structures was undertaken [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. In 1994, John Moult and his colleagues initiated the critical assessment of techniques for protein structure prediction (CASP) experiments [49] which allowed a worldwide survey of comparative modeling algorithms for a bona fide blind prediction of protein structures [50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%